Interactively Mediating Experiences of Mindfulness Meditation - Vidyarthi, Jay; Riecke, Bernhard E. (International Journal Of Human-Computer Studies, 2014)
Highlights • Sonic Cradle is a persuasive medium designed to encourage mindfulness meditation. • Sonic Cradle suspends the body in a dark chamber where respiration influences music. • After trying the system, 39 participant interviews were systematically analyzed. • Qualitative findings suggest an experience comparable to mindfulness meditation. • Technology has the potential to increase wellbeing by introducing people to mindfulness. Abstract Sonic Cradle is a human–computer interaction paradigm designed to foster meditative attentional patterns. A user׳s body is suspended comfortably in a completely dark sound chamber while the interaction paradigm subtly encourages them to focus on their breathing to summon and progressively shape an abstract immersive sound experience. Basic interpretive qualitative methods with a purposive sample of 39 participants were used to systematically analyze interview data after a 15-min experience of the system. Results suggest that this persuasive medium can pleasantly encourage an experience comparable to mindfulness by consistently inducing a calm mental clarity and loss of intention. Surprisingly, participants also reported perceptual illusions, feelings of floating, and emotional responses. Mounting evidence implies mindfulness meditation as an effective practice for self-regulation; this study represents a first step toward realizing technology׳s potential to increase wellbeing by introducing people to this psychologically beneficial contemplative practice.
Keywords: Riecke; Riecke_2014; immersion; jay-vidyarthi; journalPaper; sonic-cradle